TOPICS AND KINDS OF TEXT NEEDED IN IMPROVING COLLEGE STUDENTS’ READING SKILL A STUDY OF NEED ANALYSIS AS AN INITIAL STEP TO DEVELOP GENERAL ENGLISH COURSE MATERIAL BASED ON BLENDED LEARNING - Muhammad Affandi Arianto; Senorica Yulia Sari; Delvi Wahyuni (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2018)
The importance of English language course to be taught in most universities in Indonesia resulted in a policy especially at Universitas Negeri Padang in providing English as a General Course (MKU-English) to be taught to students. The importance of learning material in MKU-English attracted the attention of researchers to analyze the needs of students related to teaching materials such as what is the suitable teaching material to be taught to large classes such as MKU which contains students from various departments. This needs analysis research aims to identify and explain the needs of students that will be as the initial foundation of development of teaching materials covering aspects of the topics, types of text, and skill and components of the language. The samples of this research were 381 students who were taking MKU-English in academic year 2017-2018. By analyzing the results of the questionnaire that has been disseminated, it was found that the students wanted a variety of topics. In addition, students need to learn the types of argumentative and descriptive texts to support their reading skills. In addition, teaching materials are also emphasized on the integration of language components such as grammar.